The Relationship Of Learning Value Of Educational Field Experience With The Interest Of Unp Family Welfare Education Students To Become Teachers - Fuada, Miftahul; Yulastri, Asmar (Jurnal Pendidikan Tata Boga dan Teknologi, 2022)
This study aims to determine whether there is a relationship between the learning outcomes of Educational Field Experience Practices and the interest of UNP Family Welfare Education students to become teachers. This type of research is descriptive quantitative research with a correlational approach. The population in this study were students of the Family Welfare Department of Family Welfare Education Study Program class of 2016, which amounted to 125 students, consisting of 56 students of Catering and 69 students of Fashion Design. The sampling technique used is Proportional Random Sampling technique, the sample is 56 students consisting of 25 culinary students and 31 fashion students. Data collection techniques using questionnaires that have been tested for validity and reliability. The data analysis technique uses Pearson Product Moment Correlation Analysis. The results of the study concluded that there was a positive and significant relationship between the learning outcomes of Educational Field Experience Practice and the interest of Family Welfare Education students to become teachers with a positive correlation coefficient of 0.720 and a significant 0.042 <0.05, then Ha was accepted.